Carbon-13 Nuclear Magnetic Resonance Spectra of Heterocyclic Compounds - Desmaison, Martine (My University, 1973)
Experimental carbon-13 nuclear magnetic resonance chemical shifts are given for substituted 1,3-dioxanes, tetrahydrofurans, dihydro-2-furanones and succinic anhydrides. The experimental data are used to improve and extend the carbon-13 chemical shift prediction parameters which allow one to estimate with considerable accuracy unknown chemical shift values.
Keywords: carbon-13, nuclear, magnetic, resonance, heterocyclic